Are Emotion Regulation Strategies Associated With Visual Attentional Breadth for Emotional Information in Youth? - Boelens, Elisa; Van Beveren, Marie-Lotte; De Raedt, Rudi; Verbeken, Sandra; Braet, Caroline (Frontiers in Psychology, 2021)
Attentional deployment is currently considered as one of the most central mechanisms in emotion regulation (ER) as it is assumed to be a crucial first step in the selection of emotional information. According to the broaden-and-build theory, positive emotions are associated with attentional broadening and negative emotions with attentional narrowing toward emotional information. Given that ER strategies relying on attentional deployment (i.e., rumination, cognitive reappraisal and distraction) have the possibility to influence positive and negative emotions by (re)directing one’s attention, there could be an association with one’s attentional scope. The current study investigated the association between the general (trait) use of three specific ER strategies and visual attentional breadth for positive, negative, and neutral information in a selected sample of 56 adolescents (M = 12.54, SD = 1.72; 49% girls) at risk for developing psychopathology. First, participants self-reported on their overall use of different ER strategies. Next, the previously validated Attentional Breadth Task (ABT) was used to measure visual attention breadth toward emotional information. No evidence was found for the relationship between 2 specific ER strategies (i.e., cognitive reappraisal and rumination) and visual attentional breadth for neutral, positive and negative emotional information. Surprisingly, “distraction” was associated with visual attentional narrowing, which was unrelated to the valence of the emotion. These unexpected results indicate the multifaceted relationship between trait ER, distraction specifically, and visual attentional breadth for emotional information. Future research, especially in younger age groups, could further elaborate on this research domain.